A Flexible Dual-Analyte Electrochemical Biosensor for Salivary Glucose and Lactate Detection - Mingyang Liu; Muqun Yang; Muxue Wang; Han Wang; Jing Cheng (Biosensors, 2022)
Electrochemical biosensors have been widely applied in the development of metabolite detection systems for disease management. However, conventional intravenous and fingertip blood tests are invasive and cannot track dynamic trends of multiple metabolites. Among various body fluids, saliva can be easily accessed and is regarded as a promising candidate for non-invasive metabolite detection. Recent works on the development of electrochemical biosensors for monitoring salivary metabolites have demonstrated high sensitivity and wide linear range. However, most of this research has been focused on salivary detection of a single metabolite. Here, we present a dual-channel electrochemical biosensor for simultaneous detection of lactate and glucose in saliva based on a flexible screen-printed electrode with two working electrodes. The sensitivities of glucose and lactate channels were 18.7 μA/(mM·cm2) and 21.8 μA/(mM·cm2), respectively. The dual-channel biosensor exhibited wide linear ranges of 0–1500 μM for the glucose channel and 0–2000 μM for the lactate channel and the cross-talk between the two detection channels was negligible, which made it adequately suitable for sensing low-level salivary metabolites. Such attractive characteristics demonstrate the potential of this dual-analyte biosensor in the development of wearable devices for monitoring disease progression and fitness.